2021
DOI: 10.3390/microbiolres12030052
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Zika Virus Replication with Amantadine and Rimantadine Hydrochlorides

Abstract: Zika virus (ZIKV) is a mosquito-borne flavivirus in which human infection became relevant during recent outbreaks in Latin America due to its unrecognized association with fetal neurological disorders. Currently, there are no approved effective antivirals or vaccines for the treatment or prevention of ZIKV infections. Amantadine and rimantadine are approved antivirals used against susceptible influenza A virus infections that have been shown to have antiviral activity against other viruses, such as dengue viru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The established MTC values for the derivative compounds 1A and 1R of the ion-channel inhibitors Amantadine and Rimantadine are 400 µg/mL. The results obtained by us for the toxicity of compounds 1A and 1R are similar to the results obtained by other author groups using another cell line for the toxicity of Amantadine and Rimantadine [40]. The determined CC50 is above 400 µg/mL.…”
Section: Antiviral Activitysupporting
confidence: 87%
“…The established MTC values for the derivative compounds 1A and 1R of the ion-channel inhibitors Amantadine and Rimantadine are 400 µg/mL. The results obtained by us for the toxicity of compounds 1A and 1R are similar to the results obtained by other author groups using another cell line for the toxicity of Amantadine and Rimantadine [40]. The determined CC50 is above 400 µg/mL.…”
Section: Antiviral Activitysupporting
confidence: 87%
“…Arias et al have reported in vitro antiviral efficacies of amantadine and rimantadine hydrochlorides against ZIKV strains (ZIKV CIET‐01, ZIKV MR766, and ZIKV R103451), DENV‐1 Angola, and YFV 17D. [ 100 ] Compound 51 displayed maximum efficacies toward ZIKV CIET‐01 and ZIKV R103451. Chayrov et al have synthesized a class of amino acids substituted adamantane derivatives and evaluated their antiviral activity against influenza virus A (H3N2).…”
Section: Pharmacological Activities Of Adamantane‐based Hybridsmentioning
confidence: 99%